Feasibility analysis of quantitative evaluation of residual renal function in children with hydronephrosis by ultrasonic VOCAL technique - DU Ying; LI Yang; CHEN Yu-long (Linchuang shenzangbing zazhi)
Objective To investigate the feasibility of quantitative evaluation of residual renal function by three-dimensional ultrasound volumetric measurement(VOCAL)technique in children with hydronephrosis.Methods From June 2014 to June 2017,74 children with unilateral hydronephrosis were enrolled in our Department of Urology.VOCAL technique was used to measure renal volume(RV),renal parenchymal volume(RPV),and renal parenchymal volume ratio(RPVR).Glomerular filtration rate(GFR)was determined by dynamic renal arterial scintigraphy.The ultrasonic measurement parameters in the affected and healthy kidneys and different degrees of hydronephrosis were compared.The correlation between the ultrasonic measurement parameters and GFR was analyzed.Results As compared with the healthy kidney,the RV in the affected kidney increased,and the GFR decreased,the difference was statistically significant(P<0.05),and there was no significant difference in RPV(P>0.05).The HVR in grade 2 of hydronephrosis was significantly higher than in grade 1(P<0.05),GFR,RV,and RPV had no significant difference(P>0.05).By comparing grade 3 with grade 2 or grade 4 with grade 3,GFR and RPV were all decreased,RV and HVR were all increased,and the difference was statistically significant(P<0.05).Pearson correlation analysis showed that RV was not associated with GFR(r=0.191,P>0.05),RPV was linearly correlated with GFR(r=0.342,P<0.05),and HVR was highly linearly correlated with GFR(r=0.783,P<0.05).When HVR≥0.45 and the GFR dropped below50%,the area under the ROC curve was 0.88,the sensitivity was 98.4%,and the specificity was 73.3%.Conclusions VOCAL technique is feasible in evaluating residual renal function in children with hydronephrosis.